Impact of anxiety and depression on morbidity and mortality of patients with coronary syndrome - Denise Meira Altino; Luiz Antonio Nogueira-Martins; Maria Aparecida Batistão Gonçalves; Alba Lucia Bottura Leite de Barros; Juliana de Lima Lopes
ABSTRACT Objective: Evaluate the impact of anxiety and depression on morbidity and mortality of patients with acute coronary syndrome. Method: Retrospective cohort study, with follow-up of two years, conducted with 94 patients. The morbidity and mortality (readmission, myocardial revascularization, and death) was evaluated immediately after discharge and after one and two years. Anxiety and depression were evaluated by the State-Trait Anxiety Inventory and by Beck's Depression Inventory. The Kaplan-Meier estimator and the Logrank test were used. The significance level adopted was 0.05. Results: We observed that 76.6% of the patients did not present symptoms of depression or had mild signs, while 78.8% had low to moderate anxiety. The symptoms of depression and anxiety were not related to morbidity (need for MR p=0.098 and 0.56, respectively; readmission p=0.962 and 0.369, respectively) and mortality (p=0.434 and 0.077, respectively). Conclusion: No relationship was found between levels of anxiety and depression with the morbidity and mortality of patients.